The Importance Of Sports Games In The Physical Education System - Samadova Uktabar Khasanovna (Genius Journals, 2025)
In the article physical upbringing sports games in the system place and importance about word Sports games features, sports from sports games in training of those involved health improve tasks solution to do and to them sports propaganda their work take to go issues cover received
Keywords: physical education; sports; games; physical education exercises